Al3+-Induced growth of α-Co(OH)2 nanoplates as high-capacity supercapacitors and water oxidation electrocatalysts. Issue 7 (13th January 2017) - Liu, Rongmei; Jiang, Zixiang; Ma, Juping; Ni, Lu; Sun, Xueying; Liu, Yong; Chen, Haixing; Liu, Qi
Abstract : α-Co(OH)2 nanoplates with good capacitive properties and OER activity were synthesized by using Al 3+ ions as a structure-inducing agent. Abstract : In this paper, we report a metal ion-induced synthesis of α-Co(OH)2 nanoplates as high-capacity supercapacitors and water oxidation electrocatalysts, which were synthesized by using metal ions of Al 3+ as a structure-inducing agent through hydrothermal treatment. When used as electrode materials in supercapacitors, α-Co(OH)2 nanoplates exhibit good capacitive properties of 709.1 F g −1 at a current density of 1 A g −1, maintaining 95.8% of the initial capacity at the current density of 5 A g −1 after 1000 cycles. The α-Co(OH)2 nanoplates can effectively oxidize water, showing excellent OER activity with a small overpotential of 348 mV at the current density of 10 mA cm −2 and a large mass activity of 28.2 A g −1, much higher than that of the β-Co(OH)2 particle electrocatalyst (0.2 A g −1 ). These results provide a new and facile approach to fabricating high-performance electrodes for supercapacitors and water oxidation electrocatalysts.